O Narrador: considerações sobre a arte de contar histórias na cidade - Siqueira, Giuliano Tierno de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Esta tese trata de pensar a arte de contar histórias na cidade. O título é uma alusão à clássica obra de Walter Benjamin,O Narrador. Considerações sobre a obra de Nikolai Leskov, texto de 1936. Foram consideradas nessa investigação a experiência do pesquisador/contador de histórias e de alguns narradores brasileiros que atuam em contexto urbano. Em diálogo com pensadores, educadores, artistas contemporâneos, o foco central da discussão é o paradoxo existente entre o ressurgimento da figura do contador de histórias nas cidades nas últimas décadas - com vistas à valorização da palavra pública e de retomada do encantamento dos encontros por meio da partilha de histórias - e o seu alinhamento com as práticas artísticas e performáticas ligadas ao entrenimento. Esse último ponto, pensado à luz das ideias de Guy Debord (1931-1994), sobretudo em relação ao conceito de Sociedade do Espetáculo; e, Christoph Turcke (1948 -) e sua tese sobre a Sociedade Excitada. Para responder esse explícito paradoxo entre a necessidade do exercício da partilha pública da palavra e sua concomitante armadilha sensório-espetacular nos dias de hoje, o leitor encontrará o relato de experiência do pesquisador/contador de histórias (articulado às experiências que são comuns a tantos outros narradores que surgiram nas cidades); um diálogo fictício entre o pesquisador e os autores referenciais dessa pesquisa; e, por fim, o desdobramento de outras questões pertinentes aos posicionamentos ético, estético, poético e político do contador de histórias na atualidade.

This thesis aims to reflect on the art of storytelling in the city. The title aludes to Walter Benjamin’s classic, The Storyteller. Reflections on the work of Nikolai Leskov (from 1936). There were taken into consideration in this research investigation the experience of the researcher/storyteller and of some Brazilian raconteurs who act in the urban contexts. In a dialogue with philosophers, art and educators and contemporary thinkers, the central focus of this discussion is the paradox between the rebirth of the storyteller within cities in the last decades (with regards to the appreciation of the public word and of the enchantment) and, it’s alignment with the cultural practices of entertainment. This last point, thought under the enlightenment of Guy Debord (1931-1994) and his considerations about the spectacle society; and, Christoph Turcke (1948) thoughts about the excited society. This paradox will be seen on the interviews conducted with the storytellers, and also by the bibliographical research that approaches the art of contemporary storytelling. To reach this paradox it was necessary to retell some of the pathways for formation and acting of storytellers who will appear on the research as Brazilian icons of this comeback of the art of storytelling within cities, besides understanding the roots that originated the storytelling styles we see nowadays on social and public spaces, along with the kinds of stories which will mostly compound this raconteurs repertoires. Through a fictional dialogue between the researcher and the reference authors of this research it is explicit the paradox pointed above and also unfolded from other relevant questions referring to the ethical, aesthetical, poetical and political positioning of the storyteller nowadays.
El narrador: consideraciones sobre el arte de la narración en la ciudad
Keywords: Contador de histórias urbano; Performances narrativas; Palavra pública; Urban storyteller; Storytelling styles; Repertoire of storytellers within cities